Personal expressions in the Russian texts translated from a Japanese Manga - T. Ninomiya (Әл-Фараби Атындағы Қазақ Ұлттық Университеті хабаршы шығыстану сериясы, 2021)
This study is a series of Descriptive translation studies of the Japanese comic, “Hadashi no Gen (Barefoot Gen)” written by Keiji Nakazawa. Members of Project Gen translated the comic from the Japanese language to the Russian language twice. The present researcher compared the Japanese original version, the Russian old version, and the Russian new version. He made use of the three-phase methodology proposed by Toury (1995). This study analyzed personal expressions in the comic: i.e., First Person, Second Person (Pronoun use), Second Person (Vocative use), and Third Person. To analyze these expressions, the eight translation strategies were set up: i.e., Transcription, Phonetic or Morphological Adaptation, Literal Translation, Transposition, Modulation, Expansion, Deletion, and Partial Deletion. By and large, the result showed that Literal Translation was used in the Russian old and new versions most frequently. When investigating which of the Russian old version and the Russian new version put more emphasis on Source Text-oriented translation (or Target Text oriented translation), the present researcher revealed the following: fundamentally, the Russian two versions had the same tendency in terms of the translation strategies of personal expressions; furthermore, in detail, the Russian new version put more emphasis on the Target Text-oriented translation than the Russian old version. As a cause of why the new version valued the Target Text-oriented translation more than the old version, the present researcher presumed that the members of the Project Gen failed in the sale of the old version. The old version was not popular in Russia. The members made the text easier to read for Russian native speakers, to sell many of the translated comics. As part of the new translation, the members modified personal expressions in the old version, putting emphasis on the Target Text-oriented translation.